Barriers to ideal outcomes after pediatric liver transplantation. (25th July 2019) - Ng, Vicky Lee; Mazariegos, George V.; Kelly, Beau; Horslen, Simon; McDiarmid, Sue V.; Magee, John C.; Loomes, Kathleen M.; Fischer, Ryan T.; Sundaram, Shikha S.; Lai, Jennifer C.; Te, Helen S.; Bucuvalas, John C.
Abstract: Long‐term survival for children who undergo LT is now the rule rather than the exception. However, a focus on the outcome of patient or graft survival rates alone provides an incomplete and limited view of life for patients who undergo LT as an infant, child, or teen. The paradigm has now appropriately shifted to opportunities focused on our overarching goals of "surviving and thriving" with long‐term allograft health, freedom of complications from long‐term immunosuppression, self‐reported well‐being, and global functional health. Experts within the liver transplant community highlight clinical gaps and potential barriers at each of the pretransplant, intra‐operative, early‐, medium‐, and long‐term post‐transplant stages toward these broader mandates. Strategies including clinical research, innovation, and quality improvement targeting both traditional as well as PRO are outlined and, if successfully leveraged and conducted, would improve outcomes for recipients of pediatric LT.